Structure and variability of the boundary current in the Eurasian Basin of the Arctic Ocean. (July 2015) - Pnyushkov, Andrey V.; Polyakov, Igor V.; Ivanov, Vladimir V.; Aksenov, Yevgeny; Coward, Andrew C.; Janout, Markus; Rabe, Benjamin
Abstract: The Arctic Circumpolar Boundary Current (ACBC) transports a vast amount of mass and heat around cyclonic gyres of the deep basins, acting as a narrow, topographically-controlled flow, confined to the continental margins. Current observations during 2002–2011 at seven moorings along the major Atlantic Water (AW) pathway, complemented by an extensive collection of measured temperatures and salinities as well as results of state-of-the-art numerical modeling, have been used to examine the spatial structure and temporal variability of the ACBC within the Eurasian Basin (EB). These observations and modeling results suggest a gradual, six-fold decrease of boundary current speed (from 24 to 4 cm/s) on the route between Fram Strait and the Lomonosov Ridge, accompanied by a transformation of the vertical flow structure from mainly barotropic in Fram Strait to baroclinic between the area north of Spitsbergen and the central Laptev Sea continental slope. The relative role of density-driven currents in maintaining AW circulation increases with the progression of the ACBC eastward from Fram Strait, so that baroclinic ACBC forcing dominates over the barotropic in the eastern EB. Mooring records have revealed that waters within the AW and the cold halocline layers circulate in roughly the same direction in the eastern EB. The seasonal signal, meanwhile, is the most powerful mode of variability in the EB, contributing up to ~70% of the total variability in currents (resolved by moorings records) within the eastern EB. Seasonal signal amplitudes for current speed and AW temperature both decrease with the eastward progression of AW flow from source regions, and demonstrate strong interannual modulation. In the 2000s, the state of the EB (e.g., circulation pattern, thermohaline conditions, and freshwater balance) experienced remarkable changes. Results showing anomalous circulation patterns for an extended period of 30 months in 2008–2010 for the eastern EB, and a two-core AW temperature structure that emerged in this region of the Arctic Ocean in the most recent decade, suggest a shift of the EB toward a new, more dynamic state. This also likely suggests that the EB interior will become more susceptible to future climate change. Evaluating properties of the ACBC, its temporal variability at time scales from a season to several years, and possible governing mechanisms, this study contributes to a better understanding of Arctic Ocean circulation. Highlights: A six-fold decrease in boundary current speed (from 24 to 4 cm/s) was registered on the along-slope route between Fram Strait and the Lomonosov Ridge. Mooring observations show vertical coherence of flow in Atlantic Water and halocline layers in the Eurasian Basin. In the eastern Eurasian Basin, amplitude of seasonal changes constitutes up to ~70% of the mean boundary current speed. Prevailing anticyclonic (i.e., shallow-to-left) circulation was found for 2008–2010 in the eastern Eurasian Basin. The cause, we hypothesize, was the large-scale reconstruction of temperature and salinity fields.